2018
DOI: 10.1080/02813432.2018.1499581
|View full text |Cite
|
Sign up to set email alerts
|

Variations in drug-related problems detected by multidisciplinary teams in Norwegian nursing homes and home nursing care

Abstract: The frequency of unclear documentation and adverse reactions found in the homecare setting is alarming. This is an important issue given the trend in aged care towards caring people in their own homes. Further research is warranted to explore how different care settings may influence the safety of pharmacotherapy for older persons. Key Points Drug related problems are a significant cause of concern among patients receiving home nursing care as well as for patients living in nursing homes. The findings of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
(49 reference statements)
2
27
0
4
Order By: Relevance
“…In a recent study using the same classification tool as we did, Devik et al found a mean of 3.7 MRPs per nursing home resident. They found that most of the MRPs related to unnecessary medication use (28%) or to need for additional medications (22%), while we identified most problems in relation to unnecessary medication use, to high doses and drug interactions [9].…”
Section: Medication Use and Medication Related Problemsmentioning
confidence: 68%
See 3 more Smart Citations
“…In a recent study using the same classification tool as we did, Devik et al found a mean of 3.7 MRPs per nursing home resident. They found that most of the MRPs related to unnecessary medication use (28%) or to need for additional medications (22%), while we identified most problems in relation to unnecessary medication use, to high doses and drug interactions [9].…”
Section: Medication Use and Medication Related Problemsmentioning
confidence: 68%
“…The interdisciplinary team agreed upon 62% of the MRPs identified by the pharmacist, which is lower, but within range of the acceptance rate of 71% reported by Devik et al [9]. The purpose of the MRP classification tool was to investigate areas of sub-optimal quality in relation to the residents' entire medication regimen.…”
Section: The Interdisciplinary Team Collaborationmentioning
confidence: 76%
See 2 more Smart Citations
“…Compliance-related problems describe instances when a client prefers not to take a medication, does not understand how to use a medication, or cannot afford a medication. A client is experiencing a compliancerelated problem if he or she does not understand how to use an inhaler or prefers not to take a medication to treat a condition [1], [4], [5].…”
Section: Common Mrps and Success Of Pharmacy Visits At Homementioning
confidence: 99%